Zirconocene-Initiated Intramolecular Hydride Transfer in N-Isoalkyl-Substituted Propargylamines - Ramazanov, Ilfir R.; Kadikova, Rita N.; Saitova, Zukhra R.; Dzhemilev, Usein M. (Synlett, 2018)
The unusual transformation of N-isoalkyl-substituted propargylamines into alkenylamines under the action of Cp2ZrCl2 and organoaluminum compounds (Me3Al, EtAlCl2) has been observed. The proposed mechanism, involving the N-isoalkyl-substituted propargylamine undergoing zirconocene-initiated intramolecular hydride transfer was supported by B3LYP/6-31G(d)/LanL2DZ calculations.
Keywords: alkenylamine; hydride transfer; negative hyperconjugation; propargylamine; zirconocene cation